Content Structure Analysis of Merdeka Curriculum on Chemical Equilibrium Topic in F Phase - Siti Sarah; Faizah Qurrata Aini; Zonalia Fitriza (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The implementation of the merdeka curriculum as an improvement and replacement for the previous curriculum needs to be studied on the structure and depth of its learning content. This study aims to describe the suitability of the content structure of chemical equilibrium material based on Bloom's Revised Taxonomy and university textbooks as standards. The research method used is descriptive qualitative to describe the object according to the data and information obtained. The research design uses the Model of Educational Reconstruction (MER) by Reinders Duit which focuses on Content Structure Analysis. The data analysis technique uses the Miles and Huberman model by collecting, reducing, presenting, and concluding data. There are research instruments: knowledge, skill, and attitude level analysis sheets, as well as content standard analysis of chemical equilibrium topic. The results of curriculum analysis show a deriving in operational verbs from the level of knowledge, skills, and attitudes based on the Pancasila profile. For content analysis, it is found that the depth and breadth of chemical equilibrium learning materials from the Cambridge book grade XI of the Ministry of Education and Culture and the University textbook by Brady are consistent but the development of the material sequence is different. The sub-chapter on equilibrium constants Kc and Kp should be the prerequisite material before learning the concept of equilibrium shift.